Coordinated power management and optimized techno-enviro-economic design of an autonomous hybrid renewable microgrid: A case study in Egypt. (1st October 2020) - Kotb, Kotb M.; Elkadeem, M.R.; Elmorshedy, Mahmoud F.; Dán, András
Graphical abstract: Highlights: A multi-objective optimization model for the optimal design of HMGESs is proposed. The optimization model includes energy, economic and environmental aspects in the assessment. SPV/WDG/DslG/Battery is the most economic, sustainable, and ecologically favorable option. A power management strategy is applied efficiently on the optimized system to safeguard system power quality. Abstract: Currently, the global gives a unique awareness of sustainable development by exploiting renewables to provide the people with affordable and clean energy and preserve the climate. This paper proposes a methodical and explicit framework of four phases, to design an autonomous hybrid renewable energy system in a community area in Egypt: preliminarily assessment, design optimization analysis, findings evaluation, and power-quality assessment. In the first three phases which performed by HOMER Pro® software, five hybridization scenarios are evaluated and compared regarding their life-cycle cost, carbon outflows, and reliability to distinguish the extraordinary scenario to supply the addressed community area. Contrary to the majority of studies that suffice only the first three phases, the fourth phase is proposed to perform a power-quality valuation based on a power management strategy (PMS). The results reveal that the optimal configuration consists of a photovoltaic generator, wind-driven generator, diesel-genset, battery-bank, and a power converter with the minimum net present cost of 351, 223 $ and energy cost of 0.2262 $/kWh among all configurations. The optimal system has a negligible capacity shortage of 0.0955% and produces the least amount of emitted gases by 50.43 tones/year due to the high renewable fraction (57%). Moreover, the optimal proposed system can recover the invested money after only 3.4 years. The proposed PMS profitably harmonized the system's energy exchange, kept sufficient reserve energy at all times, and maintained the system stability under various meteorological and load disturbances. This can be verified from the superior stabilization of the dc-bus, load voltage and frequency during the examined disturbances.